Analisis Persepsi Ragam Hias Melayu Sebagai Identitas Interior di Lobi Rektorat Universitas Lancang Kuning - Masda Ulfa Arianti; Tesa Beta Hariandini; Isrina Indah (DIVAGATRA - Jurnal Penelitian Mahasiswa Desain, 2025)
Lancang Kuning University is an educational institution that strengthens the Riau Malay cultural identity through its architectural and interior elements. One part that reflects this identity is the lobi of the rectorate building, which functions as a guest reception center and a symbol of academic leadership. This study aims to analyze the perception of the use of Malay decorative motifs as a factor in shaping cultural identity in the interior design of the Unilak Rectorate lobi. The methodological approach used includes direct observation of Malay decorative elements and interviews to understand their influence on the user experience of the space. The results show that the applied Malay decorative motifs not only strengthen aesthetic and traditional values but also increase the sense of attachment to local culture. This research highlights that cultural elements in interior design are integral to the identity of educational institutions and provides insights into the role of spatial design in shaping users’ perceptions and experiences. The primary benefit of this research is to support the development of locally culture-based interior design that can enhance the university's image.